Integrated emergy and economic evaluation of the dominant organic rice production systems in Jiangsu province, China - Gao, Pinglei; Wang, Haoyu; Sun, Guojun; Xu, Qiang; Dou, Zhi; Dong, Erjia; Wu, Wenge; Dai, Qigen (Frontiers in Plant Science, 2023)
Changing from conventional to organic farming might have fewer negative environmental impacts because of the avoidance of synthetic fertilizer and chemical pesticides. In this study, the economic viability and environmental and sustainability performance of the four dominant organic (rice-green manure rotation (RG), rice-duck co-culture (RD), rice-crayfish co-culture (RCF) and rice monoculture (RM)) and one conventional (rice monoculture (CRM)) rice production modes were evaluated in Jiangsu Province, China. Compared with the CRM mode, organic rice production increased economic benefits density and improved the economic benefit of crop land and irrigation water use. With the lowest total emergy input and the highest rice yield, the CRM mode showed the highest ecological efficiency in converting resources to total available energy content and nutrition density unit among the five rice production modes. However, the RCM mode showed higher environmental pressure and lower sustainability than the four organic modes due to the larger proportion of nonrenewable emergy input. The RM mode was the most uneconomic organic rice production mode with the highest cost input and the lowest product output but had relatively higher sustainability due to the higher proportion of renewable resources to total emergy inputs. Compared with the RM mode, the value-to-cost ratio, economic benefit density and benefit-cost ratio were increased in the RG, RD and RCF modes. Although the RD and RCF modes had higher efficiency in converting resources to total nutrition density units and monetary value, they imposed higher environmental pressure with a lower renewable fraction and emergy sustainability index than those in the RM mode. The RG mode had higher emergy utilization efficiency and the highest renewable fraction and emergy sustainability index among the four organic rice production modes. Considering the ecological and economic effects, the RG mode was conducive to improving the economic viability and sustainability of organic rice production.